2009
DOI: 10.1021/la903007v
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive PEG-Based Polymer Layers: Surface Characterization with AFM Force Measurements

Abstract: Thermoresponsive polymer-coated surfaces based on poly(2-(2-methoxyethoxy)ethyl methacrylate-co-oligo(ethylene glycol) methacrylate) [P(MEO(2)MA-co-OEGMA)] allow switching between cell attachment and detachment. Here, we investigate the temperature-dependent surface interactions between the polymer coating and a colloidal probe in an aqueous medium by means of atomic force microscopy (AFM) force-distance measurements. The analysis of the adhesion forces from AFM retraction curves identifies two kinds of regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 37 publications
9
51
0
Order By: Relevance
“…As the structural change of the only a few nanometers thick polymer layer occurs considerably faster than the observed cell rounding, it is reasonable to assume that the rounding is an active process of the cells and that the kinetics of the transition of the polymer at the LCST does not play a major role. Moreover, this argument is in line with results obtained by colloidal probe measurements which suggest that the kinetics of the change of cell morphology upon the decrease of temperature is determined by cellular processes rather than by the dynamics of the transition of the polymers [20]. The assumption of an actively driven cell detachment on thermoresponsive surfaces is further supported by observations of Okano et al [21] on poly(N-isopropylacrylamide)-coatings who also described a reduced cell detachment efficiency at lower temperatures and after chemical manipulation of the cell metabolism [22,23].…”
Section: Resultssupporting
confidence: 90%
“…As the structural change of the only a few nanometers thick polymer layer occurs considerably faster than the observed cell rounding, it is reasonable to assume that the rounding is an active process of the cells and that the kinetics of the transition of the polymer at the LCST does not play a major role. Moreover, this argument is in line with results obtained by colloidal probe measurements which suggest that the kinetics of the change of cell morphology upon the decrease of temperature is determined by cellular processes rather than by the dynamics of the transition of the polymers [20]. The assumption of an actively driven cell detachment on thermoresponsive surfaces is further supported by observations of Okano et al [21] on poly(N-isopropylacrylamide)-coatings who also described a reduced cell detachment efficiency at lower temperatures and after chemical manipulation of the cell metabolism [22,23].…”
Section: Resultssupporting
confidence: 90%
“…On reduction of the suspension temperature to below the expected lower critical solution temperature of PDEGMA (<25°C), the polymer chains became hydrated and chain-extended, resulting in cell detachment from the microparticle surfaces. This phenomenon of thermoreversible bioadhesion hasbeen observed previously with grafted PEGMA polymers on various substrates, [41][42][43][44][45][46] Presto Blue viability assays with 3T3 fibroblasts cultured within the prepared colloidal gel showed that the cells proliferated and remained viable with significant increases in cell number over time from Figure S8 ESI) that the proliferation capacity on the 2D surface was lower than in the 3D gel. The total number of cells from the 3D matrices was higher compared to that for cells grown on the 2D plastic surfaces.…”
Section: Application Of Thermoresponsive Magnetic Colloidal Gels To 3supporting
confidence: 78%
“…For example, by adjusting the cell adhesion force on the substrates, the cell migration rate can be modulated by the grafting amount of poly(ethylene glycol) (PEG) [17], the brush length of poly(hydroxyethyl methacrylate) (PHEMA) [18], and the stiffness of salt-treated multilayers [19]. Because all these methods adjusted surface wettability and thus changed cellesubstrate interaction [20]. Cells migrate fastest on the surface with a moderate cell adhesion force [21].…”
Section: Introductionmentioning
confidence: 99%